Lingvokognitivnyj analiz diskursa: ponâtijno-terminologičeskij apparat issledovaniâ - Malyševa, Elena G. (Stylistyka, 2019)
This article is devoted to the linguistic and cognitive analysis of discourse. The article defines the basie terms and concepts, which are concepts and terminology by linguistic and cognitive analysis oť discourse, explores techniques for conceptual dominant discourse, discusses the various aspects of this analysis.